The Factors Influencing Economic Efficiency of the Hospital Bed Care in Terms of the Regional Allowance Organizations - Ivana Vaňková; Iveta Vrabková (Review of Economic Perspectives, 2014)
This paper aims to provide an efficiency evaluation of selected hospital bed care providers during years 2010 -2012 with respect to selected factors: The size of the hospital establishment according to number of beds, number of hospitalized patients, the average length of stay per a patient in care, total staff cost calculated per bed, total revenues calculated per bed, and total costs calculated per bed. For this purpose, hospitals providing primarily acute bed care were chosen. From the legal point of view, they are allowance organizations of a particular region. The evaluation concerns both allocative efficiency and technical efficiency. The allocative efficiency is treated from the proper algorithm point of view and it compares total costs calculated per bed with total revenues calculated per bed. A method denominated Data Envelopment Analysis was applied for the calculation of the technical efficiency of units. To be more specific, it was input-oriented model with constant returns to scale (CCR). The input parameters involve the number of beds, the average length of stay and costs per day of stay. Output parameters were as follows: Bed occupancy in days and the number of hospitalized patients. The data published by the Institute of Health Information and Statistic of the Czech Republic and by ÚFIS system (the Data Base of Ministry of Finance of the Czech Republic) were used as the source of data. The evaluation implies that only three hospitals were economically-effective: Silesian Hospital in Opava, Hospital Jihlava, and TGM Hospital Hodonín. The most significant factor influencing the efficiency was determined - the average length of stay.
Keywords: 330